Synthesis and Characterization of Anethole-lauryl Methacrylate Copolymer via Cationic Polymerization - Handayani, Desi Suci; Tahara, Alfia Uke; Firdaus, Maulidan; Suryanti, Venty; Kusumaningsih, Triana; Marliyana, Soerya Dewi; Wibowo, Fajar Rakhman; Wartono, Muhammad Widyo (Universitas Jenderal Soedirman, 2023)
The synthesis of anethole-lauryl methacrylate (LMA) copolymer had been carried out by cationic polymerization using BF3O(C2H5)2 as the initiator without the use of solvent at room temperature (28-30 °C) over atmospheric N2 conditions. Polymerization was conducted by varying LMA concentration i.e. 2%, 4%, and 6%, (w/w) with respect to the anethole weight. Structural determination of co-poly(anethole-LMA) was done using FTIR and 1H-NMR spectrophotometer. The relative molecular weight (Mv) of co-poly (anethole-LMA) was measured by an Ostwald Viscometer at room temperature. Morphological characterization and surface area analysis of co-poly(anethole-LMA) was performed using SEM and SAA, respectively. The successful synthesis of co-poly(anethole-LMA) was proven by the disappearance of vinyl group absorption at 1696, 1638, 965, and 938 cm-1 of the FTIR spectra, as well as the loss of vinyl group proton signals at 6.4-5.5 ppm in the 1H-NMR spectra. Increasing the weight of the LMA affected the characteristics of co-poly(anethole-LMA). The relative molecular weight of co-poly(anethole-LMA) was found to rise by increasing the weight of LMA. The Mv of co-poly(anethole-LMA) 2%, 4%, and 6% were 32378.62, 50611.05, and 65133.79 g/mol, respectively. The morphology of co-poly(anethole-LMA) showed that the surface distance between particles was getting tighter and the highest surface area in co-poly(Anethole-LMA) 6% was 233.80 m2/g.